FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN BALITA KE POSYANDU ANYELIR WILAYAH KERJA PUSKESMAS PEMBANTU DESA PANTAI CERMIN KABUPATEN KAMPAR - Amelia Yarsi; Rifa Yanti; Meirita Herawati; Hirza Rahmita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Visits of toddlers to integrated health posts (Posyandu) are a vital effort to monitor child growth and development. However, the frequency of these visits remains suboptimal in several areas, including Posyandu Anyelir in Pantai Cermin Village, Kampar Regency. This study aimed to determine the influence of knowledge, attitude, support from health workers, the role of health cadres, and family support on toddler visits to Posyandu. A quantitative method with a cross-sectional design was applied, involving 92 mothers of toddlers as respondents. Data were collected using a structured questionnaire and analyzed using the chi-square test. The results showed that all variables had a significant relationship with the activeness of Posyandu visits: knowledge (p=0.000; OR=4.590–96.073), attitude (p=0.003; OR=1.565–10.222), support from health workers (p=0.001; OR=1.923–12.124), the role of cadres (p=0.000; OR=4.755–37.559), and family support (p=0.001; OR=1.923–12.124). It can be concluded that all these factors significantly influence the activeness of toddler visits to Posyandu. Educational interventions, strengthening the roles of cadres and health workers, and involving the family are essential strategies to increase community participation in Posyandu activities. Kata Kunci : Toddler visits, Posyandu, knowledge, attitude, family support